A Community-Based Sensory Training Program Leads to Improved Experience at a Local Zoo for Children with Sensory Challenges - Michele Kong; Mallory Pritchard; Lara Dean; Michele Talley; Roger Torbert; Julian Maha (Frontiers Media S.A., 2017)
Sensory processing difficulties are common among many special needs children, especially those with autism spectrum disorder (ASD). The sensory sensitivities often result in interference of daily functioning and can lead to social isolation for both the individual and family unit. A quality improvement (QI) project was undertaken within a local zoo to systematically implement a sensory training program targeted at helping special needs individuals with sensory challenges, including those with ASD, Down's syndrome, attention-deficit/hyperactivity disorder, and speech delay. We piloted the program over a 2-year period. The program consisted of staff training, provision of sensory bags and specific social stories, as well as creation of quiet zones. Two hundred family units were surveyed before and after implementation of the sensory training program. In this pilot QI study, families reported increased visitation to the zoo, improved interactions with staff members, and the overall quality of their experience. In conclusion, we are able to demonstrate that a sensory training program within the community zoo is feasible, impactful, and has the potential to decrease social isolation for special needs individuals and their families.